National implementation of the Baby-friendly Hospital Initiative 2017 - Grummer-Strawn, Laurence M (World Health Organization, 2017)
A report on the incorporation of the Baby-friendly hospital initiative in various countries. Intended for professional public.
Keywords: Breast Feeding; veřejné zdravotnictví; kojení; Global Health; Infant Health; nemocnice; zdraví kojenců; politologie, politika, zdravotní politika; výživová politika; Nutrition Policy; Hospitals; Program Evaluation; celosvětové zdraví; perinatologie a neonatologie; hodnocení programu